2012
DOI: 10.1007/s00726-011-1207-5
|View full text |Cite
|
Sign up to set email alerts
|

Metabolism and neurotoxicity of homocysteine thiolactone in mice: protective role of bleomycin hydrolase

Abstract: Genetic or nutritional disorders in homocysteine (Hcy) metabolism elevate Hcy-thiolactone and cause heart and brain diseases. Hcy-thiolactone has been implicated in these diseases because it has the ability to modify protein lysine residues and generate toxic N-Hcy-proteins with auto-immunogenic, pro-thrombotic, and amyloidogenic properties. Bleomycin hydrolase (Blmh) has the ability to hydrolyze L-Hcy-thiolactone (but not D-Hcy-thiolactone) to Hcy in vitro, but whether this reflects a physiological function h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
74
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 45 publications
(75 citation statements)
references
References 50 publications
1
74
0
Order By: Relevance
“…In present study both aging and the degenerative diseases have been shown to be accompanied by lowered levels of Met and Met to Hcy ratio, most probably due to disturbed process of Hcy remethylation. At the same time, according to a recent theory, the lowered ratio of Met to Hcy may be linked to induction of arteriosclerotic lesions by Hcy with involvement of thiolactone [19]. One of the products of Met demethylation is known to involve S-adenosylmethionine (SAM).…”
Section: Discussionmentioning
confidence: 99%
“…In present study both aging and the degenerative diseases have been shown to be accompanied by lowered levels of Met and Met to Hcy ratio, most probably due to disturbed process of Hcy remethylation. At the same time, according to a recent theory, the lowered ratio of Met to Hcy may be linked to induction of arteriosclerotic lesions by Hcy with involvement of thiolactone [19]. One of the products of Met demethylation is known to involve S-adenosylmethionine (SAM).…”
Section: Discussionmentioning
confidence: 99%
“…Named for its ability to hydrolyze organophosphates like paraoxon found in insecticides, PON1 is also able to hydrolyze N-acyl-homoserine, a lactone used by pathogenic bacteria, and lipid peroxides, thereby inhibiting the formation of foam cells known to contribute to atherosclerosis [16, 2022]. …”
Section: Paraoxonase 1 and Atherosclerosismentioning
confidence: 99%
“…For example, in two studies that examined the toxicity of individual Hcy species, the free thiol Hcy was associated with endothelial dysfunction in humans, whereas much more abundant disulfide Hcy species were not [136,137]. Furthermore, Hcy-thiolactone is known to be more toxic than Hcy to cultured human endothelial cells [61] and to mice [140,141]. Furthermore, Hcy-thiolactone is known to be more toxic than Hcy to cultured human endothelial cells [61] and to mice [140,141].…”
Section: Free Reduced Homocysteinementioning
confidence: 99%